THE TEACHERS' CLINIC. - Kaulback, Frank S.; Bastable, Charles W. (The Accounting Review, 1955)
Abstract The development of the balance-sheet approach is justly regarded as a significant contribution to the teaching of accounting, in that it permits education in accounting to be developed logically, rather than by the study of a series of rules that can have little meaning until the complete accounting cycle has been presented. Nevertheless, the balance-sheet approach is not without its critics, most of whom are primarily concerned with the fact that this method tends to plant in the mind of a student the incorrect thought that a balance sheet shows what a business is "worth." There is other evidence to suggest the desirability of removing inventories from the current-asset category. With regard to the question on the soundness of the "lower of cost or market" rule, one should be impressed with its limited applicability. It serves the single purpose of charging a price-level loss to the period in which it occurs. This is because present accounting principles, which are founded on the assumption of a stable money, are not adequate to cope with price-level changes.